PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, DAN KOMPETENSI DIGITAL TERHADAP KINERJA GURU MELALUI MOTIVASI KERJA - Sutono; Azainil; Komariyah, Laili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Quality education requires the central role of teachers in integrating Information and Communication Technology (ICT); however, teachers’ mastery of Digital Competence in Balikpapan City still shows significant variation, creating performance disparities in the 5.0 era. This study aims to analyze the simultaneous influence of Transformational Leadership and Digital Competence on Teacher Performance, with Work Motivation as a mediating variable, representing a novelty in testing a dual mediation model. The research employed a quantitative causal method, involving a sample of 288 public junior high school teachers in Balikpapan City selected through proportionate random sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that Transformational Leadership has the most dominant direct effect on Teacher Performance (β = 0.593), followed by Digital Competence (β = 0.477). Work Motivation was found to significantly (partially) mediate both relationships. Crucially, the indirect effect of Digital Competence on Teacher Performance through Work Motivation (β = 0.283) was stronger than the indirect effect of Transformational Leadership on Teacher Performance through Work Motivation (β = 0.152). The study concludes that Work Motivation is an essential mediator, serving as a critical multiplier that transforms teachers’ digital skills into optimal performance. Practically, Transformational Leadership should focus on strengthening Digital Competence that can sustainably enhance teachers’ Work Motivation